The Role of Artificial Intelligence in Developing Planning Budgets and Enhancing the Financial Control in Insurance Companies: an Applied Study in Al-Rafidain Bank - Fadhel Abed; Laith Khaghaany; Alaa Alsharmani (Journal of Macroeconomics and Social Development, 2026)
The current research aims to measure the role of artificial intelligence in preparing planning budgets and enhancing financial control in insurance companies at Rafidain Bank, as the financial and banking sector has undergone tremendous transformations with the emergence of artificial intelligence, which has proven effective in improving the accuracy of financial data, preparing planning budgets, and enhancing financial control in insurance institutions and banks. The research relied on the analytical method in building financial reports, in addition to adopting surveys and interviews with financial experts and accountants in order to measure the level of availability of artificial intelligence, planning, and financial control. Based on this, the research produced several key findings, most notably that artificial intelligence has emerged as an essential part of the planning budget preparation process due to its contribution to collecting and analysing vast amounts of data in generating accurate and objective forecasts.